UPAYA HUMANE SOCIETY INTERNATIONAL DALAM MENDORONG PERUBAHAN KEBIJAKAN ANIMAL TESTING DI TIONGKOK MELALUI KAMPANYE BE CRUELTY-FREE - Rastania, Wayan Artesia; Priadarsini, Ni Wayan Rainy; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2019)
ABSTRACT This research explains the efforts made by Humane Society International (HSI) to encourage change of animal testing practice in People’s Republic of China. To do so, Qualitiative Research is selected as the methodology, and all research related data is acquired via secondary means or through the use of both online and printed literatures. Afterwards, the data will be analyzed using Animal Rights and Power of International Organization concepts, focusing on the power possessed by Non-Governmental Organization. At the end, the research will show the motivation behind HSI’s efforts, as well as every programs under the umbrella of a grand campaign known as Be Cruelty-Free in 2013-2016. The campaign will be seen as means to effectively implement power which later raising the awareness of Chinese society and government on the importance of protection toward so-called laboratory animals and ultimately ease the change of direction toward policy and practice of animal testing. Key Words: International organization, campaign, animal rights, power